Assessment of the knowledge level on basic and advanced resuscitation procedures in children among students of medicine - Gałka, Agnieszka; Czyż, Rafał (Journal of Education, Health and Sport, 2018)
Knowledge and skills related to providing basic and advanced resuscitation procedures to children should be well known to all healthcare workers and students of medical faculties. It is essential to teach future doctors how to react correctly in situations where the health and life of children are in danger. The aim of this work is to assess the level of knowledge of basic and advanced resuscitation procedures in children among students of medicine. Tested population consisted of 162 students of the 1st to 6th year of studies at the Faculty of Medicine of the Medical University in Wrocław.The anonymous survey created by author contained 23 questions that referred to socio-demographic data as well as basic and advanced medical knowledge. The respondents most often assessed their level of knowledge of basic resuscitation procedures in children as average (49%) and of advanced procedures as low (38%).Students received an average overall score of 9.7±2.9 points.In the section concerning basic resuscitation procedures the respondents received, on the average, 8.2±1.9 points. Only 27% of the students knew the correct answer to the question concerning the location of chest compressions in children. In the section on advanced resuscitation procedures, the students received an average score of 1.4±1.8 points out of a maximum of 7 points.It is worrying that only 68% of 5th year and 50% of 6th year students were able to give the correct value of defibrillation energy.Only 36% of 5th year and 10% of 6th year students gave the correct volume of fluid bolus in children. The knowledge level of basic and advanced resuscitation procedures in children among medicine students is insufficient.It is important to focus more on practical classes on the resuscitation of children for students.